Strategi Peningkatan Kinerja Aparatur Terhadap Pelaksanaan Pengawasan pada Inspektorat Kabupaten Ciamis - Yoppi Hidayat Jauhari; Ading Rahman Sukmara (Journal of Management and Social Sciences, 2024)
This research is motivated by the fact that the Ciamis Regency Inspectorate apparatus has not performed well in carrying out supervision in accordance with the Regulation of the Minister of Home Affairs Number 61 of 2019. In the Ciamis Regency Inspectorate, this can be seen from the results of the Ciamis Regency Inspectorate performance report, several problems were found. The purpose of this study is to determine the strategy for improving the performance of the apparatus in implementing supervision at the Ciamis Regency Inspectorate. This study used a descriptive method with a qualitative approach. The informants in this study were 4 people, namely the Inspector, Secretary of the Inspectorate, Head of Planning and Programs and representatives of regional inspectors. Data analysis was carried out on data collected from both observation and interview results. The data analysis stage was carried out with qualitative analysis. The results of the study showed that: 1) The performance of the apparatus at the Ciamis Regency Inspectorate was not optimal, this was because the Inspectorate as one of the supervisory institutions responsible to the Regent had not been able to create transparency, objectivity, more effective supervision efficiency, and more accumulative and accountable. Therefore, the Inspectorate is not only faced with the problems of functional tasks but also with coaching tasks. 2) The implementation of supervision in carrying out its activities as a supervisor of the implementation of regional government cannot be separated from the factors that influence the implementation of the supervisory function carried out on the implementation of regional government. These factors are: internal factors, namely the number of supervisory officers is still limited, and external factors, namely the availability of many mandatory tasks that must be carried out and negligence of the object of inspection. 3) The Inspectorate as an internal supervisor is required to make a major contribution to improving the quality of the implementation of Regional Government, but on the other hand, its capacity is not yet sufficient to carry out its main tasks and functions with various problems and limitations.